Elevated Pancreatic Enzymes in ICU Patients With COVID-19 in Wuhan, China: A Retrospective Study - Ding, Peili; Song, Bin; Liu, Xuelin; Fang, Xing; Cai, Hongliu; Zhang, Dingyu; Zheng, Xia (Frontiers in Medicine, 2021)
Objective: Few researchers pay attention to the elevated pancreas enzymes in COVID-19. However, with an extreme lack of medical resources, we faced several challenges related to examination and treatment during the outbreak. Did we need to change the nutrition pattern at the peak period? Was this a warning signal of multiple organ failure? The objective of this report was to pursue the truth and the underlying causes. Method: Fifty-five patients with COVID-19 admitted to the ICU of Wuhan Jinyintan hospital from January 1 to March 30, 2020, were included as the subjects in our study. All recruited patients underwent transabdominal ultrasound. Results: The median age of 55 cases was 63, with 18 females. The most common symptoms were fever and cough. Patients were divided into three groups, 3 with pancreatitis, 29 with elevated enzymes (19 with more than 3 times the upper limit of normal), and 23 without elevated enzymes. The three groups show statistical differences in hypertriglyceridemia and myalgia on admission, and mechanical ventilation and CRRT on treatment. The mortality of patients without elevated pancreas enzymes was less than the other two groups, and the discharge rate was higher than the other two groups. The possible causes for elevated enzymes could be summarized in renal impairment, gastroenteritis, shock, and oxygenation degradation. Conclusions: The incidence of elevated pancreas enzymes was not very low. Few patients developed acute pancreatitis caused by SARS-CoV-2 which excludes other causes. Increased pancreas enzymes might be associated with clinical poor outcomes. The most possible causes for elevated enzymes were gastroenteritis, respiratory failure, and shock. The measure of specific pancreas enzymes was important in patients with COVID-19 and other critical diseases with shock or respiratory failure.